1993
DOI: 10.1038/363732a0
|View full text |Cite
|
Sign up to set email alerts
|

The SCID-hu mouse as a model for HIV-1 infection

Abstract: During normal fetal ontogeny, one of the first organs to harbour CD4-positive cells is the thymus. This organ could therefore be one of the earliest targets infected by human immunodeficiency virus type 1 (HIV-1) in utero. HIV-1-infected cells and pathological abnormalities of the thymus have been seen in HIV-1-infected adults and children, and in some fetuses aborted from infected women. Studies of HIV-1 pathogenesis have been hampered by lack of a suitable animal model system. Here we use the SCID-hu mouse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
185
1
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(197 citation statements)
references
References 17 publications
10
185
1
1
Order By: Relevance
“…HIV infection of the human thymus is associated with thymic destruction and accelerated disease progression (42)(43)(44)(45)(46). Given the profound effects of IL-7 on the survival of human thymocytes, it is possible that IL-7 might prevent or attenuate HIV-mediated destruction of the thymus.…”
Section: Effects Of Il-7 On Hiv-infected and Uninfected Thymus In Scimentioning
confidence: 99%
“…HIV infection of the human thymus is associated with thymic destruction and accelerated disease progression (42)(43)(44)(45)(46). Given the profound effects of IL-7 on the survival of human thymocytes, it is possible that IL-7 might prevent or attenuate HIV-mediated destruction of the thymus.…”
Section: Effects Of Il-7 On Hiv-infected and Uninfected Thymus In Scimentioning
confidence: 99%
“…Only thymocyte samples with good viability Indeed, in SCID-hu mouse studies, [10][11][12][13][14] HIV-1 infection was (Ͼ95%) were used. Portions of each sample were used for the shown to cause drastic destruction of grafted human thy-CT assay, and to determine antigen (Ag) profiles and proliferatmuses.…”
mentioning
confidence: 99%
“…[10][11][12][13][14] These accumulated findings could conceivably be related to rapid thymic cell death phenomenon without MHC restriction to, or virus replication in, the targets by contact with some the in vitro rapid thymic cell death phenomenon we observed, and indeed they are all relevant to the better understanding HIV-1 carrier clones (notably CD8 + clones) specific to TdT + CD4 + CD8 + and/or TdT + CD4 + thymic T cell targets, of HIV-1 pathogenesis. The present in vitro study, nonetheless, demonstrates clearly including an autologous combination of parental DP cells (HPB-ALL) and their CD8 SP HIV-1 carrier progeny clones that at the clonal level, HIV-1 carrier T cell clones, which are likely present in vivo, 8,[41][42][43][44] are responsible for the profound (HPB-ALL/HIV and HPB-ALL/HIV C1) (Tables 1 and 2).…”
mentioning
confidence: 99%
“…In vitro studies have shown that HIV-1 can infect thymocytes from uninfected subjects, and in vivo studies in the SCID-hu chimera model have shown that immature thymocytes are infected by HIV-1 and implicate HIV as the direct (3)(4)(5) and indirect (6, 7) cause of thymocyte death. Although information on infection of thymocytes in vivo is limited, a report analyzing thymic tissue obtained from an infant with perinatal HIV-1 infection demonstrated infection in immature thymocytes (1).…”
mentioning
confidence: 99%